THE EFFECT OF ALOE VERA TOWARD THE NUMBER OF FIBROBLASTS ON THE WOUND INCISION OF WISTAR RAT'S (RATUS NORVEGICUS) - Fatmawati, Chusnul Nur; Retnanin, Ekowati; Wahyuni, Tavip Dwi (Journal of Vocational Nursing, 2020)
Introduction: Incision is a wound caused by a sharp object, for example in surgery. The characteristics of the wound are pain, open wounds, and the length of the wound is greater than in it. Handling the wound there are various ways, one of which is using Aloe Vera. The aim of this study was to determine the effect of topical Aloe vera gel concentration of 10%, 20%, and 40% to determine the amount of fibroblast tissue in wistar strain rats (Rattus orvegicus) in incisions. Methods: This study uses an experimental design with a sample of 75 rats divided into 5 groups; 0.9% NaCl group, 1% tulle-framycetin sulfate group, 10% Aloe vera group, 20% Aloe vera group and 40% Aloe vera group. Samples of incisional wound skin were performed on days 3.7, and 12. All data were processed and analyzed statistically using SPSS 20. Based on microscopic observations at 10 times per field of view, the highest number of fibroblasts given at NaCl was given on the day 12th is 28.98 per field of view, treatment using tulle-framycetin sulfate 1% is 34.5 per field of view, treatment using Aloe vera 10% is 17.32 per field of view, treatment using Aloe vera 20% is 33, 9 per field of view while the treatment using Aloe vera was 40% ie 18.7 per view. Results : The results of the study with the Independent T-test and Paired T-test showed that the results of fibroblast tissue between 0.9% NaCl group, 1% tulle-framycetin sulfate, 10% Aloe vera, 40% Aloe vera with 20% Aloe vera there were differences which were significant (p <0.05) where 20% Aloe vera gave effective results in the wound healing process. Conclusion : This study concluded that 20% of Aloe vera can be used as an alternative choice of wound healing. In the next study it is expected to examine the variable TGF (Transforming Growth Factor) that affects cell growth in wound healing.